2017
DOI: 10.1097/cej.0000000000000230
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of 9-cis-retinoic acid and androgen on proliferation, differentiation, and apoptosis of LNCaP prostate cancer cells

Abstract: 9-cis-Retinoic acid (9cRA), which binds to both retinoic acid receptors and retinoic X receptors, inhibits prostate cancer induction in rats and reduces growth of prostate cancer cells. However, the nature of this growth inhibition and the interactive influence of androgens are not well defined and are the subject of this report. LNCaP and PC-3 cells were cultured and treated with a range of 9cRA concentrations for 3-6 days in the absence or presence of 5α-dehydrotestosterone. 9cRA inhibited cell proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…80,81 Studies have also pointed out that cancer cells treated with 9-cis-retinoic acid induce apoptosis and inhibit cancer cell growth both in vitro and in vivo. 82,83 Moreover, retinoic acid receptor RARb, was shown to act as a tumor suppressor in lung cancer. 84 In BE patients with…”
Section: Discussionmentioning
confidence: 99%
“…80,81 Studies have also pointed out that cancer cells treated with 9-cis-retinoic acid induce apoptosis and inhibit cancer cell growth both in vitro and in vivo. 82,83 Moreover, retinoic acid receptor RARb, was shown to act as a tumor suppressor in lung cancer. 84 In BE patients with…”
Section: Discussionmentioning
confidence: 99%
“…We were able to confirm that the day-0 and day-5 stored APs showed significantly different metabolomics in their supernatants, and found that the upregulated metabolites retinoate and 9-cis-retinoic acid in day-5 stored AP supernatants were enriched in cancer-related KEGG pathways. There are also studies that indicate that retinoate and 9-cis-retinoic acid are inversely related to malignant features [22][23][24][25]. Some reports state that retinoate and 9-cis-retinoic acid both participate in the regulation of the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…It participates in retinol metabolism and can also be converted to 9‐cis‐retinal by specific regulatory enzymes. 9‐cisRA which binds to both retinoic acid receptors (RAR) and nuclear retinoid X receptors (RXR) prevented prostate carcinogenesis in rats, reduced growth and induced apoptosis of human prostate cancer cells in a dose‐dependent method . 9‐cisRA induced the downregulation of P‐glycoprotein, the overexpression of which develops MDR phenotype in L1210 lymphocytic leukemia cells .…”
Section: Discussionmentioning
confidence: 99%
“…9-cisRA which binds to both retinoic acid receptors (RAR) and nuclear retinoid X receptors (RXR) prevented prostate carcinogenesis in rats, reduced growth and induced apoptosis of human prostate cancer cells in a dose-dependent method. 33 9-cisRA induced the downregulation of P-glycoprotein, the overexpression of which develops MDR phenotype in L1210 lymphocytic leukemia cells. 34 It also directly retarded the cell cycle in a concentration-and time-dependent method in NCI-H295R adrenocortical cancer cells as well as reduced tumor growth in the in vivo xenograft model.…”
Section: -Cis-retinoic Acid Levels Correlated With Breast Cancer Cmentioning
confidence: 97%